The Psychological Impacts of Internet Pornography Addiction on Adolescents - Rr. Setyawati; Nurul Hartini; Suryanto Suryanto (Bina Nusantara University, 2020)
The research aimed to reveal the impacts by adolescents who experienced internet addiction with pornographic content. It applied a qualitative approach, namely an instrumental case study. Participants were 18-25 years old, there were six adolescents who were obtained based on the initial screening, namely self-reporting through a pornography internet addiction questionnaire. The data were collected by in-depth interviews, observation, and documentation. Thematic analysis with NVivo 12 data management was used as the data analysis technique. The results show that adolescents experience changes in cognition and affection for sexual stimulation caused by the internet with pornographic content. The impact of cognition is shown from their obsessive-compulsive thoughts on sexual content. They always have the desire to see those photos or video over again, which lead them to sleep disorders due to visualizing scenes of sexual intercourse. The impact of affection can be seen from their desire to act in sexual activity, their being so passionate and pleased after seeing pornographic content, and their expectation to feel such immense affection. Furthermore, they might find difficulty in establishing interpersonal relationships with other people and tend to withdraw themselves from the social environment.